Comparative studies of oxidative stability of edible oils by differential scanning calorimetry and oxidative stability index methods - Tan, C.P.; Che Man, Y.B.; Selamat, J.; Yusoff, M.S.A. (Elsevier, 2002)
A comparative study was conducted to determine the oxidative stability of twelve different edible oils with two different instruments: a differential scanning calorimeter and an oxidative stability index (OSI) instrument. The OSI instrument temperature was set at 110 °C. The differential scanning calorimetry (DSC) technique involved oxidation of oil samples in an oxygen-flow DSC cell. The DSC cell temperature was set at four different isothermal temperatures: 110, 120, 130 and 140 °C. A dramatic increase of evolved heat was observed with the appearance of a sharp exothermic curve during initiation of the oxidation reaction. The oxidative induction time (T0) was automatically determined by extrapolation of the downward portion of the DSC oxidation curve to the time axis. There was a good correlation (P<0.0001) between the DSC T0 and OSI values. The decrease in log10 (T0) with increasing DSC isothermal temperature was best fitted by a linear equation. DSC evidently provides a convenient way to determine the oxidative stability of various edible oils.